Bioactive Phytochemicals of Citrus reticulata Seeds-An Example of Waste Product Rich in Healthy Skin Promoting Agents - Tarfah Al-Warhi; Abeer H. Elmaidomy; Samy Selim; Mohammad M. Al-Sanea; Mha Albqmi; Ehab M. Mostafa; Sabouni Ibrahim; Mohammed M. Ghoneim; Ahmed M. Sayed; Usama Ramadan Abdelmohsen (MDPI AG, 2022)
Phytochemical investigation of Egyptian mandarin orange (Citrus reticulata Blanco, F. Rutaceae) seeds afforded thirteen known compounds, 1-13. The structures of isolated compounds were assigned using 1D and 2D NMR and HRESIMS analyses. To characterize the pharmacological activity of these compounds, several integrated virtual screening-based and molecular dynamics simulation-based experiments were applied. As a result, compounds 2, 3 and 5 were putatively identified as hyaluronidase, xanthine oxidase and tyrosinase inhibitors. The subsequent in vitro testing was done to validate the in silico-based experiments to highlight the potential of these flavonoids as promising hyaluronidase, xanthine oxidase and tyrosinase inhibitors with IC50 values ranging from 6.39 ± 0.36 to 73.7 ± 2.33 µM. The present study shed light on the potential of Egyptian mandarin orange's waste product (i.e., its seeds) as a skin health-promoting natural agent. Additionally, it revealed the applicability of integrated inverse docking-based virtual screening and MDS-based experiments in efficiently predicting the biological potential of natural products.